Pengaruh Pembiasaan Tadarus Al-Qur’an Terhadap Kemampuan Membaca Al-Qur’an Di Man 2 Kabupaten Bogor - Maknunah, Salsabyla; Supriadi, Dedi; Alfaein, Noor Isna (Peneliti.net, 2024)
This study used quantitative methods using causal methods where data collection was carried out by distributing questionnaires on the habituation of Qur'an tadarus and the ability to read the Qur'an to 62 grade XII students in MAN 2 Bogor Regency. The background of the problem in this study is the assumption that the ability to read the Qur'an in high school age students is still relatively low. So researchers want to know what things can affect the ability to read the Qur'an. The objectives of this study are (1) To find out how the habituation of Qur'an tadarus of grade XII students in MAN 2 Bogor Regency (2) To find out how the ability to read the Qur'an of grade XII students in MAN 2 Bogor Regency (3) To find out whether there is an influence of habituation of Qur'an tadarus on the ability to read the Qur'an of grade XII students in MAN 2 Bogor Regency. The results showed that: (1) The habituation of tadarus Al-Qur'an class XII in MAN 2 Bogor Regency showed the results of questionnaire statements with the lowest score of 44 and the highest score of 70. While the mean score was 59.94, and the standard deviation was 5.216. furthermore, it is classified in frequency distribution with Very Good 8%, Good 40%, Good Enough 47%, and Less 5%. So it can be concluded that the habituation of class XII Qur'an tadarus in MAN 2 Bogor Regency is included in the category of quite good. (2) The ability to read the Qur'an of grade XII students in MAN 2 Bogor Regency showed the results of the questionnaire statement, the lowest score was 43 and the highest score was 71. While the mean score is 57.06, and the standard deviation is 5,480. Furthermore, it is classified in frequency distribution with Very Good results of 6%, Good 32%, Good Enough 53%, and Less 8%. So it can be concluded that the ability to read the Qur'an class XII in MAN 2 Bogor Regency is included in the category of quite good. (3) The results of the study on the Effect of Tadarus Al-Qur'an Habituation on the Ability to Read the Qur'an Class XII in MAN 2 Bogor Regency showed that the results of the Anova test that the value was known that the calculated F value was 26,672 with a significance value of 0.00 smaller than 0.05. And looking at the results of the partial test or T test with a table t result of 2,000 and a calculated t value of 5,165. Then the calculated t result is greater than t table 2,000 with significance values of 0.00 < 0.05. So Ha was accepted and Ho was rejected. So it can be concluded that in the data there is an influence between the independent variable and the dependent variable. And judging from the results of the coefficient determination test or R Square of 0.294 which contains the understanding that the influence of habituation of Qur'anic tadarus on the ability to read the Qur'an is 29.4%. which contains the understanding that the effect of habituation of the tadarus of the Qur'an on the ability to read the Qur'an is 29.4%.